Application of Al-Wa An-Nazhair's Rule of Tarjamah Tafsiriyah on the word adz-dzikr in the translation of the Ministry of Religion of the Republic of Indonesia - Eko Sedayu; Fuadi; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2024)
This study aims to reveal the application of the rules of Al-Wujuh Wa an-Nazhair in tafsiriyah tarjamah to the word "Adz-Dzikr" in the Translation of the Ministry of Religious Affairs of the Republic of Indonesia. The rule of Al-Wujuh Wa an-Nazhair is a methodology of Qur'anic interpretation that involves a contextual understanding and holistic perspective of the verses of the Qur'an. This research uses a qualitative approach with a focus on content analysis. The data collected involved the word "Adz-Dzikr" and its context from the Translation of the Ministry of Religious Affairs of the Republic of Indonesia, as well as exploring related interpretations of the Qur'an. The results of the analysis show that the rules of Al-Wujuh Wa an-Nazhair are used to understand various dimensions of the meaning of the word "Adz-Dzikr", including historical, linguistic, and cultural contexts. The findings of this study illustrate the importance of using the rules of Al-Wujuh Wa an-Nazhair in the context of tarjamah tafsiriyah. This methodology helps to thoroughly detail and delve into the meaning of the word "Adz-Dzikr", allowing the reader to understand the message of the Qur'an better. The implications of this research can support the efforts of the Ministry of Religious Affairs of the Republic of Indonesia in providing a more in-depth and contextual translation of the Qur'an for the public.